Основные подходы к пониманию аксиологического содержания образования - Akhmedova E. M. (Педагогический опыт: теория, методика, практика, 2016)
This article discusses the main approaches to the understanding of axiological content of education. The main approaches were: cultural, historical, axiological, sociological. Adding valuable context to the content of education in favor of one of the main topics discussed in contemporary pedagogy.
Keywords: ценности; образование; компетенция; магистратура; value; competence; подход; педагогическая аксиология; pedagogical axiology; magistracy; approach education